Taxonomic study on marine ciliates from Japan, with description of a new species, Caryotricha orientalis nov. spec. (Alveolata: Ciliophora) - Hu, Yue; Suzuki, Toshikazu; Hu, Xiao-Zhong (Zootaxa, 2025)
Marine ciliates from Japan were insufficiently studied. In this work, three species of class Spirotrichea Bütschli, 1889, collected from coastal water of Nagasaki, were morphologically investigated using protargol staining method. The results revealed that one represents an unknown species, Caryotricha orientalis nov. spec., and the others can be identified as Paradiophrys irmgard (Mansfeld, 1923) Jankowski, 1978 and Actinotricha saltans Cohn, 1866, the latter two species being new records for Japan. The new species is characterized by its medium-sized body, 19 adoral membranelles, about eight cirral rows extending posteriorly to mid-body, six transverse cirri arranged in two rows, and a migratory row of four cirri as well as eight dorsal kineties. Meanwhile, supplementary data on morphology and micrographs and ecological factors were provided for two known species, which thus help to circumscribe both species and increase our knowledge about distribution.